2018
DOI: 10.1073/pnas.1719548115
|View full text |Cite|
|
Sign up to set email alerts
|

External light activates hair follicle stem cells through eyes via an ipRGC–SCN–sympathetic neural pathway

Abstract: Changes in external light patterns can alter cell activities in peripheral tissues through slow entrainment of the central clock in suprachiasmatic nucleus (SCN). It remains unclear whether cells in otherwise photo-insensitive tissues can achieve rapid responses to changes in external light. Here we show that light stimulation of animals' eyes results in rapid activation of hair follicle stem cells with prominent hair regeneration. Mechanistically, light signals are interpreted by M1-type intrinsically photose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 92 publications
1
45
0
Order By: Relevance
“…Due to the continuous advance in hair research, more and more cell types (Fig. 2), including DP cells, adipose tissue, lymphatic vessels, nerves and immune cells, are identified to be contributing to the HFSC niche [15,16,[25][26][27][28][29][30][31][32][33][34][35][36], unveiling the complexity and sophistication in the interaction of HFSCs with its environment. Since activating and inhibitory signals can both be present in the HFSC niche, the probability of HFSC activation is the readout of the summation of both activating and inhibitory signals [37,38].…”
Section: Signals and Signaling Cells Within Hfsc Nichementioning
confidence: 99%
See 2 more Smart Citations
“…Due to the continuous advance in hair research, more and more cell types (Fig. 2), including DP cells, adipose tissue, lymphatic vessels, nerves and immune cells, are identified to be contributing to the HFSC niche [15,16,[25][26][27][28][29][30][31][32][33][34][35][36], unveiling the complexity and sophistication in the interaction of HFSCs with its environment. Since activating and inhibitory signals can both be present in the HFSC niche, the probability of HFSC activation is the readout of the summation of both activating and inhibitory signals [37,38].…”
Section: Signals and Signaling Cells Within Hfsc Nichementioning
confidence: 99%
“…In catagen, the hair bulb shrinks and the lower portion of the HF regresses through a progressively shortened epithelial strand into the telogen HF. In telogen, HFSCs in the secondary hair germ and bulge remain inactivated local, systemic and even external environmental changes to adjust their activity to meet local and organismal needs [28,34,35,[43][44][45]. Since additional cells of varied functions can be incorporated singly or in combination into the HFSC niche, we think that the niche cells can be modularized and these modules can be co-opted to construct the niche (Fig.…”
Section: Functional Categorization-signaling Sensing and Message-relmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also focused on the skin, the other organ exposed to light, but observations are contradictory. While one study reported that light entrainment of skin biorhythms depends on the retina via a neural pathway and is independent of the SCN [4], another has reported that entrainment directly depends on the UV-sensitive neuropsin (OPN5) photopigments that skin cells contain [5].…”
Section: Introductionmentioning
confidence: 99%
“…The local circadian clock can affect hair follicle TA cell proliferation (Plikus et al, 2013). Light stimulation of photosensors in the eyes has been shown to induce sympathetic nerves to provoke the release of norepinephrine in the skin which activates hair growth (Fan, Chang, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%